PERANCANGAN ALAT PENANAM BIBIT PADI SISTEM PENGGERAK MANUAL DENGAN MODIFIKASI TANGKAI PENANAM - Burman Zuliawan, (2022)
The process of planting rice in Indonesia is still mostly done manually and of course requires a lot of farmer labor. But the availability of farmers began to be limited and resulted in a shortage of farmer labor. Therefore, it is necessary to use a rice seed cultivator which aims to increase the productivity of farmers' labor and facilitate the planting process. By applying calculations in determining machine elements and finite element analysis, this research resulted in the design of a manual drive system for rice seed planting with dimensions of 135cmx60cmx132cm. Using a rotary pick and planting arm as a planting system on tools that are moved manually using human power with a power of 0.18 HP. The analysis test on the frame with AISI 1045 material produces a maximum stress value of 18.9 MPa, a displacement of 5 mm, and a factor of safety of 2.1.